Réponses

2013-03-12T18:17:17+01:00

11 c) 2e^2x + e^x - 15 = 0 => e^x = 2,5 => x = ln2,5 =0,916

                                               e^x = -3 à rejeter

d)2e^4x <= 6 => e^4x <= 3 => 4x <= ln3 => x<= 1/4 ln3 = 0,274

 

e) e^(4x+5)/e^x<2 => e^(3x+5) < 2 => 3x+ 5 <ln2 => x < (ln2 - 5)/3

 

f) -2e^2x + 22e^x -56 > 0

 e^x              4              7

f(x)         -      0       +    0       -

la réponse est 4 < e^x  < 7 => ln4 < x < ln7

 

17.

1. a) S = 6ln3

2.

a) = ln(5-4) = ln1 = 0

c) = 2lne - 4lne + 2lne = 0

3.

d) x = 2592 (ln32.81)

4.a) F c'est pour tout x > 0

b) faux il suffit de remplacer x par 2par exemple

c) ln(e^3x + 1/e^3x) = ln(e^6x + 1 )/e^3x

ln(1+e^9x)/(e^6x +1)/e^3x = ln e^3x(1+e^9x)/(e^6x +1) dif de 3x donc F

d) 1+2+3+...+15 = 120 (P.A)

 donc= ln x^120 = 120lnx donc V

saut erreur ou omission